Oral complications of head and neck radiotherapy: the importance of the dental surgeon - Fernanda Carla Pantoja QUARESMA; Thais Gomes MATEUS; Juliana de Borborema Garcia PEDREIRA; Ana Paula Rodrigues COUTO; Erick Nelo PEDREIRA (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Objective: radiotherapy can lead to different adverse effects in the oral epithelial cells. This article aimed to address the main oral manifestations associated with radiotherapy of head and neck neoplasms, highlighting the importance of the dental practitioners' participation within the skilled multidisciplinary personnel to treatment. Methods: Research was conducted in the PubMed, Lilacs, SciELO, and Google Scholar databases using the keywords "head and neck radiotherapy", "oral manifestations'', and "head and neck neoplasm". Eighteen out of 533 articles published between 2015 and 2022 were selected after duplicates removal and eligibility criteria application. Results: xerostomia, hyposalivation, trismus, dysgeusia, dysphagia, dentin hypersensitivity, fungal and viral infections, radiation caries, osteoradionecrosis, mucositis, periodontal alterations, and tooth development abnormalities were the most frequently reported oral effects of radiotherapy. Conclusions: The participation of dentists in the multidisciplinary team that treats patients with head and neck cancers is fundamental since several oral complications of radiotherapy are observed. Dentists can prevent, reduce and treat some detrimental effects whether the patient is followed-up since the beginning of radiotherapy.